2015
DOI: 10.1080/13691058.2015.1048527
|View full text |Cite
|
Sign up to set email alerts
|

Working through resistance in engaging boys and men towards gender equality and progressive masculinities

Abstract: Over the last two decades, a focus on challenging and transforming dominant forms of masculinity and engaging boys and men towards gender equality and healthy masculinities has permeated South African social and health sciences and the humanities. This focus on men and boys has also been evident in intervention and activist work. However, the turn to boys, men and masculinities has not gone without resistance, contestation and contradictions. A range of localised and global realities has frustrated much of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
58
0
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(62 citation statements)
references
References 41 publications
2
58
0
2
Order By: Relevance
“…Gender norms, which are widely understood to refer to social expectations of appropriate roles and behaviors for males and females (Ratele 2015;Ridgeway and Correll 2004;Ryle 2011), are increasingly being recognized as drivers of health and well-being. The scripts for appropriate behavior based on one's sex are informed by collective beliefs about what most people do (descriptive norms), perceptions of what people ought to do (injunctive norms) and observing what popular people do (cohesive norms) (Addis and Mahalik 2003).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Gender norms, which are widely understood to refer to social expectations of appropriate roles and behaviors for males and females (Ratele 2015;Ridgeway and Correll 2004;Ryle 2011), are increasingly being recognized as drivers of health and well-being. The scripts for appropriate behavior based on one's sex are informed by collective beliefs about what most people do (descriptive norms), perceptions of what people ought to do (injunctive norms) and observing what popular people do (cohesive norms) (Addis and Mahalik 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Whereas extensive research has been conducted on how gender norms affect girls' and women's health (Firestone et al 2003; Nyamhanga and Frumence 2014; Ratele 2015), there is little, but growing, focus on the interrelationship between gender norms and men's sexual health (Addis and Mahalik 2003;Ratele 2015;Shefer et al 2015), especially among early adolescents (10-14 years), also referred to as very young male adolescents (VYMA) (De Meyer et al 2017;Gevers et al 2013;Kågesten et al 2016;Ray et al 2012). A systematic review on gender attitudes in early adolescence found that boys endorse gender norms that promote inequalities between men and women (Kågesten et al 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…act of broader class-based or other identity-based resistance and needs to be addressed in programming rather than ignored (McGeeney, 2015;Ratele, 2015). Resistance may also be linked to notions of gender equality being seen as an ostensibly "western" import, rather than being inherent to local belief systems.…”
Section: │ 1 Learning From Existing Practices Engaging With Men and mentioning
confidence: 99%
“…Daar is verskeie redes -sowel pragmaties as prinsipieel -om mans betrokke te maak by die stryd om gendergeregtigheid. Verskeie navorsingsprojekte het aangetoon dat die insluiting van mans (en seuns) tot houdings-en gedragsveranderinge met betrekking tot onder meer seks en voortplanting, lei tot hulle interaksie met hul kinders en geweld teenoor vroue (Ratele 2015). 'n Pragmatiese rede wat deur Sweetman (2013) aangevoer word, is dat mans se betrokkenheid ʼn bykomende strategie in die stryd om gendergeregtigheid bied.…”
Section: Die Rasionaal Vir Mans Se Betrokkenheid By Die Stryd Om Gendunclassified